Spatial and temporal variability of Net Primary Production on the Agulhas Bank, 1998–2018. (May 2022) - Mazwane, Sixolile L.; Poulton, Alex J.; Hickman, Anna E.; Jebri, Fatma; Jacobs, Zoe; Roberts, Mike; Noyon, Margaux
Abstract: Despite the importance of Agulhas Bank (AB) marine productivity in supporting South African coastal fisheries and shelf ecosystems, there are relatively few regional-scale assessments of its spatial and temporal variability, and most productivity studies have been limited in scale. Here we use satellite-derived Net Primary Production (NPP) rates calculated using the Vertically Generalized Production Model (VGPM) to examine the spatial and temporal dynamics of NPP over the 21-year satellite record (1998–2018) on the AB. In calculating VGPM NPP we used the OCCI Chlorophyll- a product, SST from Operational-Sea-Surface-Temperature-and-Sea-Ice-Analysis (OSTIA) and PAR from GlobColour level-3 mapped products as these represent the longest datasets that fit our extended study period. We examine spatial trends between the eastern and central AB, as well as three areas of the bank (around Port Alfred, the Tsitsikamma coast, and the 'cold ridge') that have been previously identified as contributing significantly to the overall productivity of the AB. The AB shows only a moderate degree of seasonality in NPP calculated from the VGPM, with NPP being highest in austral summer (1.7–1.8 g C m −2 d −1 ) and lowest in winter (0.9–1.0 g C m −2 d −1 ), and remains relatively high (>1 g C m −2 d −1 ) throughout the year, contrasting sharply with other shelf systems. Considered annually, NPP on the bank was 516 g C m −2 yr −1 (38 Mt C yr −1 when scaled to the total shelf area) which is higher than many other shelf systems though lower than the neighbouring Benguela system and is indicative of a moderately productive shelf system fuelled by perennial NPP. Comparing different sections of the AB from east to central bank, and including the three upwelling areas, highlighted that spatial differences in NPP were relatively limited; that these three upwelling areas made similar contributions to their relative proportion of the total shelf area, and that average rates of NPP are spatially similar across the bank, though notable high rates occur in some coastal upwelling areas. Interannual variability in NPP was relatively modest, varying between years by only ∼15% over the two decades assessed. Over the 21-year data set, there was a slight (∼0.26% yr −1 ) statistically-significant decline in calculated NPP over time for the AB as a whole, which, when examined on a pixel-by-pixel basis, indicated that most of the decline was on the central bank between 100 m and 200 m isobaths. In summer, an increase in NPP occurred on the EAB (26.5–28°E). In conclusion, the AB is a significant site of perennial moderate levels of NPP, varying little interannually and with only a slight decline in NPP over time. These factors lead to a stable environment in terms of ecosystem productivity so that the AB makes a significant contribution to the productivity of South African regional fisheries.